2021
DOI: 10.1002/adtp.202100010
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Platelet Microgels Containing Fibrin Knob B Mimetic Motifs Enhance Clotting Responses

Abstract: Native platelets are crucial players in wound healing. Key to their role is the ability of their surface receptor GPIIb/IIIa to bind fibrin at injury sites, thereby promoting clotting. When platelet activity is impaired as a result of traumatic injury or certain diseases, uncontrolled bleeding can result. To aid clotting and tissue repair in cases of poor platelet activity, synthetic platelet‐like particles capable of promoting clotting and improving wound healing responses have been previously developed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…Te fbrin-binding ability allows PLP to bind to fbrin at injury sites. We have shown in rodent trauma models that following intravenous injection, PLPs target wound sites and interface with nascent fbrin fbers to augment clotting and decrease bleeding in vivo [50,52]. We have also demonstrated that PLPs mimic platelet-mediated clot retraction, a function which stabilizes clots and promotes long term healing responses.…”
Section: Platelet-derived Inspired and Targeted Thrombolytic Therapiesmentioning
confidence: 96%
“…Te fbrin-binding ability allows PLP to bind to fbrin at injury sites. We have shown in rodent trauma models that following intravenous injection, PLPs target wound sites and interface with nascent fbrin fbers to augment clotting and decrease bleeding in vivo [50,52]. We have also demonstrated that PLPs mimic platelet-mediated clot retraction, a function which stabilizes clots and promotes long term healing responses.…”
Section: Platelet-derived Inspired and Targeted Thrombolytic Therapiesmentioning
confidence: 96%
“…Platelets can also be captured and enriched using polyphenols, [ 195 ] keratin, [ 196 ] and other materials. [ 197 ] In addition to directly capturing platelets, hemostasis can be achieved by activating platelet receptors using peptides [ 158‐159 ] or designing platelet‐mimicking materials [ 198 ] to enhance or mimic platelet function. However, these hydrogels that absorb, capture, enrich, and activate platelets can only play a passive hemostatic function.…”
Section: Design Of Bioactive Hydrogel For Hemostasismentioning
confidence: 99%
“…In this case, the lack of platelet availability from which to derive membranes was the primary obstacle (Raghunathan et al, 2022). To overcome the challenge of platelet membrane availability, some research groups coat nanoparticles with hemostatic proteins found on platelets, including fibrin knob B (Nandi et al, 2021), fibrin antibodies (Brown et al, 2014), phosphatidylserine (Sekhon et al, 2022), vWF-binding peptides, and collagen-binding peptides (Gao et al, 2020;Girish et al, 2022;Gao et al, 2023) (Table 2). These platelet-mimicking particles promote clotting, reduce blood loss, and decrease bleeding time in various models, including liver laceration, tail-clip injury, hemophilia, and human plasma from patients with coagulopathy.…”
Section: Hemostatic Biomaterialsmentioning
confidence: 99%